Exploring Body Positivity Through Instagram Discourse: A Critical Discourse Analysis of Clara Dao and Her Audience - Baiq Rahayu Kurniasih; Aprillia (ETERNAL (English Teaching Journal), 2025)
This study focuses on the feminist stylistic features of Clara Dao's Instagram discourse. A qualitative research design is employed, using Sara Mills’s feminist stylistics within the framework of Critical Discourse Analysis (CDA), which focuses on the word, sentence, and discourse levels. Data were collected through purposive sampling and documentation techniques. The subject of the study is the commentary associated with Clara Dao’s Instagram content, explicitly discussing body image issues. The data include 18 comments categorized as positive, negative, and neutral, selected based on the relevance issue of body positivity. The findings reveal that societal expectations impose certain norms and standards on women’s physical appearances. These expectations influence how women are judged and often criticized when they do not conform to dominant beauty ideals. Additionally, the construction of female identity is shown to be shaped by social norms that dictate how women should behave and present themselves in public discourse.